Colour-conscious or colour-blind? : how a group of minority Xhosa learners experience and make sense of the "colour of race" in a predominantly coloured school in Mitchells Plain, Cape Town - Henriques, Kaylene (School of Education, 2014)
Includes bibliographical references (leaves 97-107).